The impact of the different types of navigation (hierarchical - list) in the interactive media on the development of academic achievement among primary school students in the mathematics curriculum - Al-Subhi, Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2017)
Abstract: The current research aimed to identify the effect of the different types of navigation (pyramid-list) in the rich media on the development of the achievement of students in primary school in the mathematics curriculum. The research problem was limited to the following main question: In the interactive media on the development of academic achievement of primary school students? The research was applied to a sample of (60) third grade students randomly selected from Aws Bin Haritha Primary School in Madinah, Saudi Arabia, during the second semester of the second semester. In the 2017 academic year. Students were divided into two experimental groups, 30 of which were students as a first experimental group, which examined the multiplication facts by means of a hierarchical sailing pattern, and 30 students as a second experimental group. The same multiplication facts were examined by the list navigation style, Both groups have been applied The results of the study were found to be statistically significant at (0.05) between the average scores of the students in the two experimental groups. In the learning achievement test, the main effect of the variation of the navigation style (pyramid-list) in the interactive media is to the benefit of the group that implemented the application through the hierarchical navigation style. Therefore, we recommend that the results of the research be used to urge the education professionals to pay attention to the software production Which are designed by means of interactive media according to scientific technical standards and hierarchical navigation patterns to contribute to the achievement of the desired educational objectives.
Keywords: interactive multimedia; navigation patterns; hierarchical navigation pattern; list navigation pattern; academic achievement